Elamipretide (SS-31) Ameliorates Isoflurane-Induced Long-Term Impairments of Mitochondrial Morphogenesis and Cognition in Developing Rats - Wu, Jing; Hao, Shuangying; Sun, Xiao-Ru; Zhang, Hui; Li, Huihui; Zhao, Hongting; Ji, Mu-Huo; Yang, Jian-Jun; Li, Kuanyu (Frontiers in Cellular Neuroscience, 2017)
Mitochondria are supposed to be involved in the early pathogenesis of general anesthesia (GA)-induced neurotoxicity and long-term cognitive deficits in developing brains. However, effective pharmacologic agents targeted on mitochondria during GA exposure are lacking. This study explores the protective effects of mitochondrion-targeted antioxidant elamipretide (SS-31) on mitochondrial morphogenesis and cognition in developing rats exposed to isoflurane. Rat pups at postnatal day (PND) 7 were exposed to 1.5% isoflurane for 6 h following intraperitoneal administration of elamipretide or vehicle with 30 min interval. The hippocampus was immediately removed for biochemical assays. Histopathological studies were conducted at PND 21, and behavioral tests were performed at PND 40 or 60. We found that early exposure to isoflurane caused remarkable reactive oxygen species accumulation, mitochondrial deformation, and neuronal apoptosis in hippocampus. The injury occurrence ultimately gave rise to long-term cognitive deficits in developing rats. Interestingly, pretreatment with elamipretide not only provided protective effect against oxidative stress and mitochondrial damages, but also attenuated isoflurane-induced cognitive deficits. Our data support the notion that mitochondrial damage is an early and long lasting event of GA-induced injury and suggest that elamipretide might have clinically therapeutic benefits for pediatric patients undertaking GA.